Dexmedetomidine administration is associated with improved outcomes in critically ill patients with acute myocardial infarction partly through its anti-inflammatory activity - Liu, Yimou; Chen, Qian; Hu, Tianyang; Deng, Changming; Huang, Jing (Frontiers in Pharmacology, 2024)
Dexmedetomidine (DEX) is a commonly used sedative in the intensive care unit and has demonstrated cardioprotective properties against ischemia-reperfusion injury in preclinical studies. However, the protective effects of early treatment of DEX in patients with acute myocardial infarction (AMI) and its underlying mechanism are still not fully understood. This study aims to investigate the association between early DEX treatment and in-hospital mortality in patients with AMI, and to explore the potential mediating role of white blood cell (WBC) reduction in this relationship.A retrospective cohort analysis was conducted using the Medical Information Mart for Intensive Care IV (MIMIC-IV) database. Patients with AMI were divided into the DEX and non-DEX group, based on whether they received DEX treatment in the early stage of hospitalization. The primary outcome measured was in-hospital mortality. The study evaluated the association between DEX use and inhospital mortality using the Kaplan-Meier (KM) method and Cox proportional hazards model. Additionally, 1:1 propensity score matching (PSM) was conducted to validate the results. Furthermore, causal mediation analysis (CMA) was utilized to explore potential causal pathways mediated by white blood cell (WBC) reduction between early DEX use and the primary outcome.This study analyzed data from 2781 patients, with 355 in the DEX group and 2426 in the non-DEX group. KM survival analysis revealed a significantly lower in-hospital mortality rate in the DEX group compared to the non-DEX group. After adjusting for multiple confounding factors, the Cox regression model demonstrated a significant positive impact of DEX on the risk of in-hospital mortality in patients with AMI, with hazard ratios (HR) of 0.50 (95% confidence interval (CI): 0.35-0.71, p < 0.0001). PSM analysis confirmed these results, showing HR of 0.49 (95% CI: 0.31-0.77, p = 0.0022). Additionally, CMA indicated that 13.7% (95% CI: 1.7-42.9%, p = 0.022) of the beneficial effect of DEX on reducing in-hospital mortality in patients with AMI was mediated by the reduction in WBC.The treatment of DEX was associated with a lower risk of in-hospital mortality in patients with AMI, potentially due to its anti-inflammatory properties.